Towards Energy Sustainability: A Literature Review of Green Software Development - Taco Jimenez, Angelo Rodrigo (2024)
In the organizational and business environment, the increasing consumption of electrical energy by IT equipment poses a challenge in terms of cost as well as environmental impact. To address this problem, a literature review is proposed to collect and examine the most recent developments in the field of green software and their impact on energy efficiency. To carry out this literature review, the PICo search strategy was adapted and implemented and a total of 23 relevant articles were selected. In relation to the problem addressed, the concept of green software, which seeks to create efficient and sustainable programs that optimize energy consumption, has been developed. The tools and practices of sustainable software design, techniques for the development of energy-efficient systems and approaches on how to address the problems of energy consumption in data centers and cloud computing are explored.